The Influence of Complementarities between Technological and Non-Technological Innovation on New Product Export Intensity. A Study of Polish Manufactruring Firms in the Period of the Global Economic Crisis (2008-2010) - Gołębiowski, Tomasz; Lewandowska, Małgorzata (Studia Oeconomica Posnaniensia, 2017)
The goal of the paper is to assess the influence of complementarities between various modes of innovation (product, process, marketing and organizational innovation) on firms’ new products’ export intensity. The study is based on a sample of 2,795 large and medium-size innovative manufacturing firms, extracted from a Community Innovation Survey for 2008-2010 conducted by GUS in Poland. The results of the UNIANOVA procedure reveal that complementarities among product, process and marketing innovation; product and organizational innovation; product and marketing innovation; as well as among the product, marketing and organizational innovation have a positive impact on the export sales of innovative products. These results are in line with the outcomes of other studies indicating that each type of innovation may act to complement at least one other mode of innovation. We indicate that the firms should apply a multifaceted approach to innovation looking for possible complementarities among innovative activities leading to higher export performance.